Penerapan Prinsip Hukum Perjanjian dalam Kontrak Kerjasama Pengelolaan Barang Milik Daerah - Pangestika Rizki Utami (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2020)
The purpose of this study is to analyze the legal construction of the Regional Property Management Agreement. Regional property in the form of land and/or buildings and other than land and/or buildings that have been handed over by the user to the manager can be utilized optimally in order not to burden the Regional Budget and Revenues particularly maintenance costs. This article are reviewing several types of agreements by analyzing the application of the legal agreement principles in the cooperation contract in the management of property in Regional Government of Banyumas Regency. The principles of treaty law which is a concept of civil law applied in the concept of state administration law are interesting because the agreement is in the regulation of private law and public law. Government Contract is a routine legal act of government, to ensure legal certainty for the parties involved required legislation that specifically regulates commercial contracts by the government regarding procedures and authority limits.